A framework for long-term preservation of multiple relational databases - Wang, Bo (University of Ottawa (Canada), 2008)
With the advancement of information technology, more and more information is stored in digital format. Along with the evolution of computer science and its related technologies, new hardware and software emerge every day. At the same time, old hardware and software become obsolete and the data on them become inaccessible. Therefore, the development of environments to preserve digital data for the long-term (such as 50 years) has become a critical issue. This thesis focuses on how to preserve data in multiple databases for a very long time. A framework is proposed to provide a platform for archiving and retrieving the data in persistent databases. Within this framework, a multi-agent system is used to deal with the scalability and evolution of the data. An experimental environment is developed to validate the framework and to provide a base for further research. Since there is a lack of universally accepted methods to prove the success of a long-term data preservation repository, we combine theoretical proof and empirical confirmation together to address this issue.
Keywords: Computer Science.